STUDENTS’ VIEW TOWARD ONLINE CLASS FOR TEACHING SEMIOTICS IN COVID-19 PANDEMIC TERM - Amrina Sari, Riski (LPPM STBA Pontianak, 2020)
This research explains students’ views toward online classes in semiotics class during the COVID-19 pandemic term. The purposes of this research are to identify students’ views toward online classes and the other purpose is to know the benefit of online classes based on the students’ view. This research was used descriptive qualitative research. In this research students of the sixth semester of the English Literature Study Program at STBA Pontianak to be participants. The interview was used to collect the data. The findings showed that there is a positive and negative view of the participants in online learning. Positive view from the participants by doing online class they know more about technology related to media for online study. Due to the rapid change in education so online classes help the students in mastering the skill to face the era 21st century. Negative view, they said that online class is not effective as same as a face-to-face learning activity, even the lecturer has used video conference but the slow internet connection to be the problem for the students to understand what the lecturer explained. When the internet network was bad, the Google Classroom and video conference cannot work correctly, and the lack of internet quota will be a big problem for the participants. Besides, the finding of the benefit of the online class, the participants expressed that online learning is efficient in term of time, they just learning at home, through the online class they feel confident in giving an opinion about the material. In giving an opinion for the material the participants use their word, it can increase their vocabulary. The participants can interact more with the lecturer and peers comfortably than conventional learning.